Cation‐Deficiency‐Dependent CO2 Electroreduction over Copper‐Based Ruddlesden–Popper Perovskite Oxides. (22nd November 2021) - Zhu, Jiawei; Wang, Yanying; Zhi, Aomiao; Chen, Zitao; Shi, Lei; Zhang, Zhenbao; Zhang, Yu; Zhu, Yinlong; Qiu, Xiaoyu; Tian, Xuezeng; Bai, Xuedong; Zhang, Ying; et al.
Abstract: We report an effective strategy to enhance CO2 electroreduction (CER) properties of Cu‐based Ruddlesden–Popper (RP) perovskite oxides by engineering their A‐site cation deficiencies. With La2− x CuO4‐δ (L2− x C, x =0, 0.1, 0.2, and 0.3) as proof‐of‐concept catalysts, we demonstrate that their CER activity and selectivity (to C2+ or CH4 ) show either a volcano‐type or an inverted volcano‐type dependence on the x values, with the extreme point at x =0.1. Among them, at −1.4 V, the L1.9 C delivers the optimal activity (51.3 mA cm −2 ) and selectivity (41.5 %) for C2+, comparable to or better than those of most reported Cu‐based oxides, while the L1.7 C exhibits the best activity (25.1 mA cm −2 ) and selectivity (22.1 %) for CH4 . Such optimized CER properties could be ascribed to the favorable merits brought by the cation‐deficiency‐induced oxygen vacancies and/or CuO/RP hybrids, including the facilitated adsorption/activation of key reaction species and thus the manipulated reaction pathways. Abstract : Engineering A‐site cation deficiency of Cu‐based Ruddlesden–Popper perovskite oxides was an effective strategy to enhance their CO2 electroreduction properties. With La2− x CuO4− δ ( x =0, 0.1, 0.2, and 0.3) series as proof‐of‐concept catalysts, it was demonstrated that their faradaic efficiency ratios of C2+ /CH4 featured a volcano‐type dependence on the x values, with a maximum point at x =0.1.